Clinical applications of molecular imaging: imaging to guide cancer therapy - Mankoff, David (Henry Stewart Talks, 2010)
Anatomic vs. functional imaging, Functional imaging modalities, PET/CT, Radiotracer imaging, Existing cancer imaging paradigm, A new paradigm for cancer imaging, Imaging and targeted therapy, Biomarker imaging, ER expression and breast cancer endocrine therapy, Hypoxia-specific treatment, Biologic events in response to successful cancer therapy, Thymidine incorporation pathways, Bone metastasis response monitoring, FDG PET vs. bone scan, Neo-adjuvant therapy of breast cancer, Molecular imaging is a tool for measuring in vivo biology, Changes in breast cancer metabolism and blood flow predict pathologic response, Clinical trial of novel molecular imaging probes for cancer, ACRIN experimental imaging sciences committee
Reviewed at 2020/05/01